Predictors of suppurative complications for acute sore throat in primary care: prospective clinical cohort study. - Little, P; Stuart, B; Hobbs, F; Butler, C; Hay, A; Campbell, J; Delaney, B; Broomfield, S; Barratt, P; Hood, K; Everitt, H; Mullee, M; et al. (2013)
OBJECTIVE: To document whether elements of a structured history and examination predict adverse outcome of acute sore throat. DESIGN: Prospective clinical cohort. SETTING: Primary care. PARTICIPANTS: 14,610 adults with acute sore throat (≤ 2 weeks' duration). MAIN OUTCOME MEASURES: Common suppurative complications (quinsy or peritonsillar abscess, otitis media, sinusitis, impetigo or cellulitis) and reconsultation with new or unresolving symptoms within one month. RESULTS: Complications were assessed reliably (inter-rater κ=0.95). 1.3% (177/13,445) of participants developed complications overall and 14.2% (1889/13,288) reconsulted with new or unresolving symptoms. Independent predictors of complications were severe tonsillar inflammation (documented among 13.0% (1652/12,717); odds ratio 1.92, 95% confidence interval 1.28 to 2.89) and severe earache (5% (667/13,323); 3.02, 1.91 to 4.76), but the model including both variables had modest prognostic utility (bootstrapped area under the receiver operator curve 0.61, 0.57 to 0.65), and 70% of complications (124/177) occurred when neither was present. Clinical prediction rules for bacterial infection (Centor criteria and FeverPAIN) also predicted complications, but predictive values were also poor and most complications occurred with low scores (67% (118/175) scoring ≤ 2 for Centor; 126/173 (73%) scoring ≤ 2 for FeverPAIN). Previous medical problems, sex, temperature, and muscle aches were independently but weakly associated with reconsultation with new or unresolving symptoms. CONCLUSION: Important suppurative complications after an episode of acute sore throat in primary care are uncommon. History and examination and scores to predict bacterial infection cannot usefully identify those who will develop complications. Clinicians will need to rely on strategies such as safety netting or delayed prescription in managing the uncertainty and low risk of complications.